A family caregiver's relaxation enhances the gastric motility function of the patient: a crossover study. Issue 1 (December 2015) - Hasuo, Hideaki; Kanbara, Kenji; Mizuno, Yasuyuki; Nishiyama, Junji; Fukunaga, Mikihiko; Yunoki, Naoko
Abstract Background The primary purpose of this study was to assess the effect of a caregiver's relaxation on the gastric motility function of the patient. The secondary purpose was to evaluate changes in the caregiver's willingness to perform self-care following feedback on the results of the primary purpose. Methods Subjects were 26 patients with a decreased level of consciousness who received gastrostomy tube feeding and their 26 family caregivers. We compared the patient's gastric motility under the condition of having his or her hand held with and without caregiver relaxation (crossover study). Changes in the caregiver's willingness to perform self-care following feedback on the results was evaluated using self-administered questionnaires. Hypnosis was used for relaxation. The outcomes assessed for gastric motility function were the motility index and gastric emptying rate by ultrasonography examination. Results Hand-holding by the family caregiver while he or she was receiving relaxation enhanced the patient's gastric motility function. By giving feedback on the results, the caregiver's willingness to adopt self-care was increased and his or her sense of guilt was reduced. Conclusions This study suggested that a caregiver's relaxation increases the gastric motility function of the patient and that gettinng feedback including the positive results increases the caregiver's willingness to perform self-care, which consequently reduce the caregiver burden.